Keterlibatan Amerika Serikat di Kawasan Golden Crescent: Analisis Geopolitik terhadap Kejahatan Transnasional - Hilda Ariastuti (Universitas Airlangga, 2020)
This article analyzes the phenomenon of transnational organized crimein the Golden Crescent, one of the biggest producers of opium globally,and the United States’ involvement in the region. The author discussesthe production base for opium in the Golden Crescent by focusing onone country, namely Afghanistan. There are two main findings in thisstudy, namely the Golden Crescent region as a significant producer anddistributor of the global opium trade; and the business and politicalinterests that the United States brought in its invasion of Afghanistan. Oneof them is his interest in drug trafficking, which is considered to be highlyprofitable. This research concludes that the United States has politicaland economic advantage motives in its invasion of Afghanistan and itsinvolvement in the Golden Crescent.